2018
DOI: 10.1038/s41598-018-30073-w
|View full text |Cite|
|
Sign up to set email alerts
|

Enzyme-modified non-oxidized LDL (ELDL) induces human coronary artery smooth muscle cell transformation to a migratory and osteoblast-like phenotype

Abstract: Enzyme modified non-oxidative LDL (ELDL) is effectively taken up by vascular smooth muscle cells (SMC) and mediates transition into foam cells and produces phenotypic changes in SMC function. Our data show that incubation of human coronary artery SMC (HCASMC) with low concentration of ELDL (10 μg/ml) results in significantly enhanced foam cell formation compared to oxidized LDL (200 μg/ml; p < 0.01) or native LDL (200 μg/ml; p < 0.01). Bioinformatic network analysis identified activation of p38 MAPK, NFkB, ERK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 60 publications
2
31
0
Order By: Relevance
“…This is in contrast to macrophages, which readily take up oxidized LDL, acetylated LDL, ELDL, and native LDL (Figure 3 ). We demonstrated that ELDL uptake by SMC is dependent on macropinocytosis, rather than on scavenger receptors ( 61 , 62 ). Macropinocytosis is the process whereby the cell membrane folds to form vacuoles and thereby incorporates bulk cargo, such as dissolved molecules, and large volumes of extracellular fluid.…”
Section: Foam Cell Formation In Smcsmentioning
confidence: 85%
See 1 more Smart Citation
“…This is in contrast to macrophages, which readily take up oxidized LDL, acetylated LDL, ELDL, and native LDL (Figure 3 ). We demonstrated that ELDL uptake by SMC is dependent on macropinocytosis, rather than on scavenger receptors ( 61 , 62 ). Macropinocytosis is the process whereby the cell membrane folds to form vacuoles and thereby incorporates bulk cargo, such as dissolved molecules, and large volumes of extracellular fluid.…”
Section: Foam Cell Formation In Smcsmentioning
confidence: 85%
“…In vivo , ELDL represents one of the many forms of modified LDLs that form foam cells in macrophages and smooth muscles cells, and phenotypic modulations brought about by individual modified LDLs overlap significantly in an atherosclerotic milieu, making it practically impossible to differentiate between each other. By studying in vitro -generated modifications of LDL we were able to demonstrate marked differences in the transcriptome of HCASMCs upon uptake of ELDL, OxLDL, and native LDL, indicating that specific modifications of LDL in the atherosclerotic plaques may determine the biology and functional consequences in vasculature ( 62 ). A main finding was that gene expression is distinctly different between HCASMC stimulated with oxidized LDL compared to ELDL or native LDL.…”
Section: Lipoprotein Cholesterol Controls Transformation Of Smcs To Omentioning
confidence: 99%
“…Thus, modified LDL caused the gene regulation characteristic of the stimulation of phagocytosis. The current results can be compared to data on the effects of enzyme-modified non-oxidized LDL (ELDL) on vascular smooth muscle cells obtained by a different research group [43]. Their study demonstrated that ELDL could induce a phenotypic switch of the smooth muscle cells, accordingly, changing the expression of certain regulatory genes and inducing foam cell formation.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, addition of autophagy inhibitor, wortmannin (WM) attenuated the inhibitory effect of bavachin on β-GP-induced calcification and apoptosis in HASMCs. Collectively, the present study revealed that bavachin protects HASMCs against apoptosis and calcification by activation of the Atg7/ inTRODUCTiOn Vascular calcification (VC) is the pathogenic process of accumulating the crystals of calcium phosphate with in the blood vessel (Hofmann Bowman and McNally, 2012;Sun et al, 2012;Yahagi et al, 2017;Chellan et al, 2018;Benjamin et al, 2019). VC has been recognized as a marker of atherosclerotic plaques, which involves a complex pathological process, and has very high morbidity and mortality (Thompson and Towler, 2012;Asmat et al, 2016;Kay et al, 2016).…”
mentioning
confidence: 68%